Co-Treatment With Resveratrol and FGF1 Protects Against Acute Liver Toxicity After Doxorubicin Treatment via the AMPK/NRF2 Pathway - Xu, Xianchou; Liu, Qingbo; Li, Jiahao; Xiao, Mengjie; Gao, Ting; Zhang, Xiaohui; Lu, Guangping; Wang, Jie; Guo, Yuanfang; Wen, Peinan; Gu, Junlian (Frontiers in Pharmacology, 2022)
Doxorubicin (DOX), an anthracycline type of chemotherapy, is an effective therapy for several types of cancer, but serious side effects, such as severe hepatotoxicity, limit its use currently. Accordingly, an effective therapeutic strategy to prevent DOX-related hepatotoxicity is urgently needed. Through the inhibition of oxidative stress, fibroblast growth factor 1 (FGF1) is an effect therapy for a variety of liver diseases, but its use is limited by an increased risk of tumorigenesis due to hyperproliferation. Resveratrol (RES), a natural product, inhibits the growth of many cancer cell lines, including liver, breast and prostate cancer cells. Therefore, this study explored whether and how RES in combination with FGF1 can alleviate DOX-induced hepatotoxicity. The results showed that RES or FGF1 alone improved DOX-induced hepatic inflammation, apoptosis, fibrosis and oxidative stress, and these adverse effects were further attenuated after treatment with both RES and FGF1. Mechanistically, both in vivo and in vitro results showed that RES/FGF1 reduced oxidative stress and thereby alleviated liver injury by promoting nuclear translocation of nuclear factor erythroid 2-related factor 2 (NRF2) and subsequently upregulating expression of antioxidant proteins in an adenosine monophosphate-activated protein kinase (AMPK)-dependent manner. Together our results not only demonstrate that co-treatment with RES and FGF1 significantly inhibited DOX-induced hepatic inflammation, apoptosis and fibrosis, but also that co-treatment with RES and FGF1 markedly suppressed DOX-induced hepatic oxidative stress, via targeting the AMPK/NRF2 pathway and subsequently ameliorating hepatic dysfunction. Thus, the combination of RES and FGF1 may provide a new therapeutic strategy for limiting DOX-induced hepatotoxicity.